PENGARUH DIGITALMARKETING DAN INOVASI PRODUK TERHADAP PENINGKATAN VOLUME PENJUALAN PADA USAHA KECIL DI KOTA MAKASSAR - St. Rukaiyah; Syamsuddin Bidol; Derry Suryadi (Jurusan Manajemen FEB UHO, 2024)
This study aims to determine the effect of digital marketing and product innovation on increasing sales volume in small businesses in Makassar. This study is a quantitative study, using a descriptive analysis method. The population in this study were small business actors in Makassar. The sample in this study amounted to 88 samples based on the equal distribution of each sub-district visited. The data collection technique used a questionnaire with a linear multiple regression analysis technique. The results of this study indicate that digital marketing partially has a positive and significant effect on sales volume, product innovation partially has no positive and insignificant effect on sales volume. Digital marketing and product innovation simultaneously have a positive and significant effect on sales volume. These findings provide information about the need for digital adaptation among small businesses.